Cholera - The Grim Reality of Under-development - D.N. Durrheim; G.A. Ogunbanjo; L. Blumberg; K.H. Keddy (South African Family Practice)
Cholera is a severe diarrhoeal illness caused by certain strains of Vibrio cholerae, which can lead rapidly to dehydration and death. Communities dependent on water contaminated with human faeces and those with poor sanitation are very vulnerable to cholera epidemics. Although theVibrio cholerae Ol El Tor strain presently circulating in southern Africa is multi-drug resistant and currently available vaccines offer inadequate proteccion, cholera can be pre-vented by simple cost-effective measures, including chlorination or sustained boiling of drinking water. The key to cholera management is aggressive fluid replacement with the correct fluids. The latter strategy is so effective that a cholera death may be viewed as a health system failure deserving formal review. The only sustainable solution to the scourge of cholera is fundamental economic and social development with the provision of safe water and adequate sanitation for all communities.